Blood-based biomarkers in breast cancer: From proteins to circulating tumor cells to circulating tumor DNA - Michael J Duffy; Enda W McDermott; John Crown (Tumor Biology)
Biomarkers are the key to personalized treatment in patients with breast cancer. While tissue biomarkers are most useful in determining prognosis and upfront predicting response to therapy, circulating protein biomarkers such as CA 15-3 and carcinoembryonic antigen are mainly used in monitoring response to endocrine or chemotherapy in patients with advanced disease. Although several centers measure biomarkers in asymptomatic patients following curative surgery for primary breast cancer, the clinical utility of this practice is unclear. Promising new biomarkers for breast cancer include circulating tumor DNA and circulating tumor cells. In contrast to circulating protein biomarkers, measurement of circulating tumor DNA–based biomarkers is potentially useful in identifying mechanisms of resistance to ongoing therapies as well as identifying new targets for further treatment. To increase clinical utility, both the established and emerging circulating biomarkers should where possible be incorporated into randomized trials evaluating new therapies in patients with breast cancer.